A Benzocaine‐Induced Local Near‐Surface pH Effect: Influence on the Accuracy of Voltammetric Cocaine Detection. Issue 1 (17th December 2020) - de Jong, Mats; Sleegers, Nick; Schram, Jonas; Daems, Devin; Florea, Anca; De Wael, Karolien
Abstract: This work describes a local induced near‐surface pH effect (pHS ) arising from the presence of one analyte, leading to an influence or even suppression of redox signals of a second analyte present in solution. This concept and its impact on voltammetric sensing is illustrated by focusing on the detection of cocaine in the presence of the common adulterant benzocaine. An in‐depth study on the observed interference mechanism and its specificity for benzocaine and not for other adulterants was performed through the use of multiple electrochemical strategies. It was concluded that the potential shift and loss of intensity of the square‐wave voltammetric cocaine signal in the presence of benzocaine was caused by a local pHS effect. A cathodic pretreatment strategy was developed to nonetheless allow accurate cocaine detection. These insights are useful for explaining unidentified phenomena involving compounds with properties similar to benzocaine in voltammetric electroanalysis. Abstract : Adulterant interference : Voltammetry interference is often induced by adsorption processes or signal overlap of interferants. We show that less common phenomena could also occur through the examination of benzocaine‐adulterated cocaine samples. The presence of benzococaine hampers cocaine detection through a benzocaine‐induced near‐surface pH‐effect, locally acidifying the electrode surface region. A solution is provided through cathodic pretreatment strategies.